Pensamento abissal, colonialidade e as artes visuais em Cuiabá - Sanchez, Daniel Pellegrim (2015)
Articulated with the idea of Boaventura de Sousa Santos that modern Western thinking is an abysmal thought, this work proposes to verify the possible persistence of coloniality devices, divisions of social reality and epistemological dominance in the visual arts in Cuiabá, discussing issues related to racism, exploitation and other forms of violence or dehumanization. Additionally, aims to provide theoretical frameworks and tools for the ongoing construction of concepts, relationships and networks to be used to enhance and build decolonial aesthesis and subjectivities. This work is constituted by the study of the notions of coloniality and coloniality of the art, as well as by the investigation of this phenomenon in the art circuit in Cuiabá. According to Anibal Quijano (2000), coloniality is constitutive of the colonial matrix of power and results from a racial/ethnic classification followed by hierarchy that is imposed on the world's population and which operates in several spheres, planes and dimensions, including materials and subjectives of social scale and existence. The so-called epistemic racism, in turn, refers to the hierarchy of domination where the knowledge produced by Western individuals is considered as superior to knowledge produced by non-Western individuals. In art, these hierarchizations occur through the dualisms "classical" and "popular", "regional" and "universal", among others, as well as through categorizations as primitive, naive, crude, handmade, ethnic, cabocla, weird art etc. In Cuiabá there is no undergraduate degree in visual arts, but there are a lot of ("popular") self-taught artists; there are few cultural equipment and generally the sector is administered with low budget, almost without exchange policies. The lack of interest of the public sector plus the decorative direction or "spectacular" that the private sector refers to the visual arts in the local circuit g enerate insurmountable obstacles for some artists, establishing a world apart, of isolation, invisibility or, as Aníbal Quijano said, "a dead end" for those that target a trajectory within institutions, equipment, events, authorized/official circuits. Circuits that, with some exceptions, see the "South of the world" as less able, subaltern with respect to their knowledge, techniques and arts. With regard to Brazil, this hierarchy, with its values and procedures, is reproduced internally in the relations between the Sao Paulo and Rio de Janeiro art circuit with the other cities of the country. Inspired by the concept of the ―single thought‖ of Milton Santos, we call the authorized/official circuit by single path. The cuiabano paradigm of arts generates many concerns and anxieties that are demanding efforts of decolonization and legitimation of other visual production modes. Thus, we propose, in the wake of Mignolo, to conduct actions guided by resistance thoughts, notions such as "border thinking", of "epistemic disobedience" and "decolonial aesthesis", which will unhook us from the obligation to tread the single path of the hegemonic circuit, repositioning us, redefining, or constituting multi-paths in circuits others.